Beyond material reward: A holistic-transcendental human resource mamagement model for pesantren institutions - Kudri Kudri; M. Mas’ud Said; Supriyanto Supriyanto (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose − This study aims to analyze the strategies for improving the quality of human resources (HR) in Pesantren (traditional Islamic boarding schools) through the integration of spiritual values and modern management principles. Amid the pressures of modern educational standards, there is a strategic need for Pesantren to transform their HR management without losing their traditional essence. Method − This research employed qualitative case study design. Data was collected through in-depth interviews with 8 key informants—including foundation secretaries, university rectors, and school principals—as well as participatory observation and document analysis. The data analysis followed the interactive model of Miles, Huberman, and Saldana. Findings − The findings reveal that HR transformation is achieved through three strategic pillars: (1) Value-based recruitment that prioritizes organizational loyalty and Ahlussunnah wal Jama’ah (mainstream Sunni Islamic traditions) values alongside academic linearity; (2) Integrated capacity building through cross-sector partnerships; and (3) A transcendental motivation system that balances material rewards with spiritual fulfillment (seeking divine blessing). The integration of these elements establishes the Holistic-Transcendental HRM Model. This article contributes to the HRM literature by demonstrating that spiritual values can function as the core operating system of institutional resilience, offering a highly sustainable alternative to conventional, secular material-based motivation.